2014
DOI: 10.1093/neuonc/nou174.86
|View full text |Cite
|
Sign up to set email alerts
|

O10.05 * Final Analysis of the Belob Trial (A Randomized Phase Ii Study on Bevacizumab Versus Bevacizumab Plus Lomustine Versus Lomustine Single Agent in Recurrent Glioblastoma) and First Radiology Review Results

Abstract: INTRODUCTION: Treatment options for recurrent glioblastoma remain limited, with only modest activity of second line chemotherapy. Despite the absence of well controlled trials, bevacizumab is widely used for recurrent glioblastoma. Nonetheless, it remains unclear if the high response rates observed after treatment with bevacizumab translate into an overall survival (OS) benefit. We report the first randomized phase II trial on bevacizumab in recurrent glioblastoma with a control arm without bevacizumab. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…No active combination partner for bevacizumab has been identified in the setting of progressive disease, albeit in uncontrolled or non-comparative trials, suggesting that bevacizumab monotherapy should be administered outside clinical trials. Preliminary data indicate that the combination of bevacizumab and CCNU may be superior to either agent alone, 53 suggesting that this combination warrants further exploration as planned in a phase III trial by the EORTC.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…No active combination partner for bevacizumab has been identified in the setting of progressive disease, albeit in uncontrolled or non-comparative trials, suggesting that bevacizumab monotherapy should be administered outside clinical trials. Preliminary data indicate that the combination of bevacizumab and CCNU may be superior to either agent alone, 53 suggesting that this combination warrants further exploration as planned in a phase III trial by the EORTC.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…60 In this study, patients in the combination arm had better outcomes than patients in either of the monotherapy arms, with the primary endpoint of 9-month OS rate of 38% versus 43% versus 59%, respectively. In addition, the median OS was 8 months versus 8 months versus 11 months, respectively, with an impressive improvement in the 6-month PFS rate at 18% versus 11% versus 41%, respectively.…”
Section: Newly Reported Bevacizumab Trialsmentioning
confidence: 66%
“…32,[59][60][61][62][63][64][65][66][67][68] The randomized phase 2 GLARIUS trial compared bevacizumab, irinotecan, and radiotherapy versus standard temozolomide and radiation in patients with O 6 -methylguanine-methyltransferase (MGMT)-unmethylated, newly diagnosed glioblastoma. 59 This study found the combination of bevacizumab and irinotecan with radiotherapy to be more favorable than standard therapy, with the 6-month PFS rate reported at 79.5% versus 41.3%, and a mean PFS of 9.7 months versus 6 months, respectively.…”
Section: Newly Reported Bevacizumab Trialsmentioning
confidence: 99%
“…A Dutch study explored combining bevacizumab with lomustine [29]. The BELOB study trial randomly assigned patients to bevacizumab, lomustine, or bevacizumab plus lomustine at first recurrence of GBM.…”
Section: Bevacizumab-evidencementioning
confidence: 99%